INFLUENCE OF CARDIOSPERMUM HALICACABUM LEAF EXTRACT ON MEMBRANE BOUND ENZYMES IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - Veeramani, Chinnadurai; Al-Numair, Khalid S.; Chandramohan, Govindasamy; Alsaif, Mohammed A.; Pugalendi, Kodukkur Viswanathan (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Cardiospermum halicacabum L. has been proven scientifically to possess anti-inflammatory, antihyperglycemic, antioxidant, antiglycation, analgesic and antipyretic activities. It also has been used in Ayurveda and folk medicine for the treatment of rheumatism, fever and earache. Objective: In the present study, we investigated whether the Cardiospermum halicacabum leaf extract (CHE) can improve the membrane bound enzymes activity by streptozotocin (STZ)-induced diabetic rats. Methods: Diabetes was induced in male albino Wistar rats by intraperitonial administration of STZ. The CHE was administered orally to normal and STZ-diabetic rats for 45 days. Results: There were a marked decrease in the activities of membrane bound phosphatases such as total ATPases, Na+/K+-ATPases, Mg2+-ATPases and Ca2+-ATPases in the erythrocytes and tissues of STZ-induced diabetic rats. Oral administration of CHE to diabetic rats significantly increased the activities of these enzymes towards near normalcy. Conclusions: Thus, the present study indicates that the beneficial role of membrane bound enzymes in STZ-induced diabetic rats. The antihyperglycemic, antioxidant and antihyperlipidemic properties of CHE (Veeramani et al., 2008; Veeramani et al., 2010) could be helpful to maintain the levels of membrane bound enzymes in STZ-induced diabetic rats showing the membrane stabilizing property of extract.